1990
DOI: 10.3146/i0095-3679-17-2-1
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Seed Mass to Oil and Protein Contents in Peanut (Arachis hypogaea L.)1

Abstract: Seed mass, oil and protein contents are important quality traits in peanut (Arachis hypogaea L.). Sixty-four genotypes were grown for four seasons to study genetic variation and character association between these three traits. Graded seed samples of 33 genotypes were further studied for possible variation within genotype among grades for oil and protein contents. No significant association of seed mass with percent oil or protein contents was observed among the 64 genotypes. However, oil and protein contents … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
17
1

Year Published

1992
1992
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 5 publications
11
17
1
Order By: Relevance
“…This could indicate that in genotypes with slightly reduced oil and increased protein content, nutritive value of seeds could be higher, due to lower phytate and increased GSH content. This was supported by the findings of Dwivedi et al [12], who also observed negative correlation between oil and protein content in peanut seeds.…”
Section: Resultssupporting
confidence: 80%
See 2 more Smart Citations
“…This could indicate that in genotypes with slightly reduced oil and increased protein content, nutritive value of seeds could be higher, due to lower phytate and increased GSH content. This was supported by the findings of Dwivedi et al [12], who also observed negative correlation between oil and protein content in peanut seeds.…”
Section: Resultssupporting
confidence: 80%
“…Obtained results indicated that seeds of examined peanut landraces could be considered as high oil and protein food, consisting of about 66.6% to 74.2% oil + protein content. Dwivedi et al [12] ascertained that oil and protein content negatively correlate in peanut seeds, which was confirmed with our results, where high oil genotypes, like P1, P7, P8, P9, and P10 have also the lowest protein content. Compared to genotypic variations, environmental factors have shown to have more pronounced effect on variations in oil content of peanut seeds [11].…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…In groundnut breeding program selections are carried out either for high oil (for oil milling) or high protein and low oil (for food and confectionary uses) to meet two distinct end-uses. Similar observations were also reported by others (Dwivedi et al, 1990, Sarvamangla et al, 2010. Hundred seed weight had significant negative association with oil content (r g =-0.34 & r p =-0.20), and significant positive association with protein content (r g =0.36 & r p =0.20).…”
Section: Genotypic and Phenotypic Correlation Between Traitssupporting
confidence: 81%
“…Correlations between oil content and seed mass, pod weight, and pod length were not significant. Dwivedi et al [5] determined that high oil content can be maintained when indirectly selecting for large seed size. Other studies have reported negative correlations between seed size and oil content in peanut [6,7].…”
Section: Introductionmentioning
confidence: 99%